Ovarian tissue cryopreservation and transplantation: 20 years experience in Bologna University - Fabbri, Raffaella; Vicenti, Rossella; Magnani, Valentina; Paradisi, Roberto; Lima, Mario; De Meis, Lucia; Rossi, Stefania; Raimondo, Diego; Casadio, Paolo; Venturoli, Stefano; Maffi, Michela; Seracchioli, Renato (Frontiers in Endocrinology, 2022)
Objective: To report the 20-year experience in ovarian tissue cryopreservation (OTC) and ovarian tissue transplantation (OTT) of the Bologna clinical center (Bologna, Italy). Design: Retrospective cohort study. Patients: 1026 pediatrics and women aged between 2 and 38 years who underwent OTC and OTT between January 2002 to January 2022. Results: Of the 1026 patients, 234 (22.8%) were pediatrics (≤ 17 years, Group 1) and 792 (77.2%) were adult women (range 18-38 years, Group 2). In Group 1, 180 (76.9%) patients had malignant diseases and 54 (23.1%) had non-malignant diseases. In Group 2, 746 (94.2%) patients had malignant diseases and 46 (5.8%) had non-malignant diseases. No real complications were observed during surgery. In all the samples analyzed most of the follicles were in the resting stage, while only a few follicles were growing. In both fresh and thawed samples, follicular density was higher in Group 1 than in Group 2 (p < 0.01). Regardless of age, good preservation of follicles and stroma was observed in fresh and thawed ovarian tissue by histological and immunohistochemical analyses (estrogen and progesterone receptors; Ki67 and Bcl2 markers; TUNEL). To date, out of 1026 total women, 812 (79.1%) had their tissue stored. Sixty-eight (6.6%) patients died from their primary disease. Twenty-four (2.3%) women performed 33 OTTs between December 2011 and January 2022. Restoration of menstruation was observed in 15 out of 17 menopausal women. Six pregnancies were achieved, two hesitated in abortion and four in the birth of healthy babies. Conclusion: OTC is the only fertility preservation technique applicable in pre-pubertal/pediatrics and in adult patients when stimulation for oocytes/embryos cryopreservation is not possible. The reported data can help future patients and physicians in their discussions and decisions about the need and possibilities of preserving ovarian function.